THE EFFECT OF HAND MASSAGE ON POSTOPERATIVE PAIN IN PATIENTS WHO HAD LUNG SURGERY: A QUASI-EXPERIMENTAL STUDY WITH A CONTROL GROUP - ÖZDEMİR, Aysun and ÖZKAN, Meral (Göbeklitepe Medical Science Journal, 2021)
Objective: This study was conducted to determine the effect of hand massage on surgical pain in patients who had lung surgery Material and Method: 34 patients who met the criteria for inclusion in the study and were selected by random sampling method were included in the intervention group and 34 patients were included in the control group. Information about the patients’ descriptive characteristics and pain severity were collected at the first stage. A total of 20 minutes of hand massage was given to each patient in the intervention group by the first researcher. Monitoring of pain and vital signs was performed in patients in the intervention group before the massage and 5, 30, 60 and 90 minutes after the massage. For the patients in the control group, it was waited for the duration of the massage applied to the intervention group. Then, they were reassessed at minutes 5, 30, 60 and 90. Chi-square, t-test in independent groups, variance analysis (ANOVA) tests were used in the analysis of the data. Findings: Measurements of patients in the intervention group after massage showed a statistically significant decrease in pain severity, blood pressure and respiratory values compared to before massage. However, no significant change in pulse values was detected. In patients in the control group, there was a significant increase in blood pressure values. Conclusion: Combined with routine treatment and care, hand massage was found to be effective in reducing the severity of pain, blood pressure and respiratory values in patients who had lung surgery.